RETRACTED: Environmental Benefits From Carbon Tax in the Chinese Carbon Market: A Roadmap to Energy Efficiency in the Post-COVID-19 Era - Wei, Ran; Ayub, Bakhtawer; Dagar, Vishal (Frontiers in Energy Research, 2022)
Because of China's global responsibilities to address climate change, the country has made a commitment to limiting future emissions growth through policy measures like funding mitigation research and regulating energy efficiency requirements directly. Extensions of these policies, such as the measures to improve energy efficiency, use of carbon taxes, and changes to the mix of electricity generation in the country, are also of interest to the China. This paper applied a Computable General Equilibrium (CGE) model to examine the effects of such energy efficiency and climate change policy options in Post COVID-19 Era in the China economy. The study findings show that even modest measures can have significant effects on emissions with marginal economic impacts given the current level of development in the China electricity generation and transportation sectors. It is estimated that a 5 RMB/per tonne carbon tax will reduce emissions by 4.1 % and GDP by 0.27 %. Emissions drop by 8.2% and GDP drops by 0.54% when energy efficiency increases by 2 % across the China economy, respectively. As a final result, a 5% shift away from burning coal would reduce emissions by 9.0 %, while GDP would rise by 1.3 %. It has been shown that even low carbon taxes can encourage a notable cleaner energy system.